Semi-empirical model of a copper bromide vapor brightness amplifier - Trigub M. V. Maksim Viktorovich (2024, 2024)
We propose the semi-empirical mathematical model of the brightness amplifier based on the self-terminating transitions in laser active media. The model is applied to the copper bromide vapor brightness amplifier. The feature of the model is that it allows one to distinguish the amplified spontaneous emission and amplified input optical signal. Due to that we have managed to study the “real” gain and theoretical maximum of contrast for the brightness amplifier depending on temporal and energy characteristics of the input optical signal.